ANALYSIS OF IMPLEMENTATION OF TPACK BY TEACHERS THROUGH DISTANCE LEARNING AT JUNIOR HIGH SCHOOL IN MEDAN - R A Sihombing; G A Manurung; L A Simanjuntak (UNIVERSITAS NEGERI MEDAN, 2021)
This research aims to analyze the application of the TPACK framework by teachers in distancelearning at junior high schools in Medan. In this research also used a qualitative descriptive methodby providing a google form questionnaire to 10 junior high school teachers in the city of Medan.The data was obtained based on the answers to questions from 10 junior high school scienceteachers, where 7 teachers were public school educators and the other 3 teachers were educators inprivate schools from different schools. The process of collecting data through a questionnairecontaining questions that must be filled in by the teacher about their agreement or disagreementwith the questions given in the questionnaire (Likert scale). The questions made are invincible withthe TPACK aspect. Based on the instruments that have been developed, researchers have obtainedthat the teachers already know and apply TPACK in distance learning well through theunderstanding and abilities possessed by the junior high school science teachers in carrying out thelearning process in the classroom, especially on the topic of temperature and heat.